2004
DOI: 10.1111/j.1523-1755.2004.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic patterns established with capillary electrophoresis and mass spectrometry for diagnostic purposes

Abstract: The data indicate that capillary electrophoresis with mass spectrometry coupling provides a promising tool that permits fast and accurate identification and differentiation of protein patterns in body fluids of healthy and diseased individuals, thus enabling diagnosis based on these patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
180
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(189 citation statements)
references
References 19 publications
3
180
1
5
Order By: Relevance
“…These patterns can be used for diagnostic purposes, since each renal disease produces a specific and typical urinary polypeptide pattern. The discrimination between different primary renal diseases was high with a sensitivity and specificity above 90% [41,54]. These results indicate that a "common biomarker", which should display unique characteristics (presence/absence or signal intensity) in each sample from patients with a defined kidney disease does not exist.…”
Section: Biomarker Discovery In Urinementioning
confidence: 77%
See 3 more Smart Citations
“…These patterns can be used for diagnostic purposes, since each renal disease produces a specific and typical urinary polypeptide pattern. The discrimination between different primary renal diseases was high with a sensitivity and specificity above 90% [41,54]. These results indicate that a "common biomarker", which should display unique characteristics (presence/absence or signal intensity) in each sample from patients with a defined kidney disease does not exist.…”
Section: Biomarker Discovery In Urinementioning
confidence: 77%
“…As evident from recent reports, this appears to be correct [12,41,[54][55][56], but a serious obstacle to this venture is the variability of polypeptides examined. Using CE-MS we documented that polypeptides in urine change significantly during the day, most likely as a consequence of physical activity, diet, smoking, etc.…”
Section: Biomarker Discovery In Urinementioning
confidence: 92%
See 2 more Smart Citations
“…However, no single polypeptide was identified that would be characteristic for a specific disease and simultaneously absent in all control samples [207]. Urine of patients with kidney diseases provided 27 exclusive polypeptides and 13 others, present in control, were missing [122,212,215,216]. Similarly, CE-MS/MS was used to analyze urinary samples from 112 patients with type II diabetes.…”
Section: Urinary Proteinsmentioning
confidence: 99%